Electrochemical Experiment to Evaluate the Impact of Multistage Load and Osmotic Pressure on Anchor Bolt. (11th February 2022) - Sun, Guanglin; Hu, Jiangchun; Wang, Hongfang; Li, Dewei
Abstract : In this paper, uniaxial compression tests, multistage loading tests, and electrochemical tests were adopted to investigate the strain characteristics, failure characteristics, and electrochemical impedance of anchor bolts in a cement-gypsum composite. The uniaxial compression test results showed that the uniaxial compressive strength σ c of the three specimens were 4.4 MPa, 4.0 MPa, and 3.1 MPa, respectively, under three different osmotic pressures. The analysis of the multistage loading tests revealed that the directions of most cracks were approximately consistent with the load-bearing direction. Moreover, the existence of osmotic pressure increased the creep deformation capacity of the specimen; the greater the osmotic pressure, the stronger the deformation capacity of the specimen. The curvature relationship of the total strain curve of the three specimens was KS12 > KS22 > KS32, and the total strain curve of S32 was close to a straight line. When comparing the creep strain variation characteristics of the three specimens, it was found that, with the increase of osmotic pressure, the proportion of creep strain within the total strain gradually increased, while the proportion of corresponding elastic strain gradually decreased. Compared with the specimen before failure, the electrochemical test in the failure stage proved the variability of the Bode curves and Nyquist curves. When the osmotic pressure was 0.15 Mpa, the Bode diagram of specimen S32 in the low frequency band showed a large jump, which was stable after entering the high frequency band.